2018
DOI: 10.1101/376632
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Commonly-used FRET fluorophores promote collapse of an otherwise disordered protein

Abstract: The dimensions that unfolded proteins, including intrinsically disordered proteins (IDPs), adopt at low or no denaturant remains controversial. We recently developed an innovative analysis procedure for small-angle X-ray scattering (SAXS) profiles and found that even relatively hydrophobic IDPs remain nearly as expanded as the chemically denatured ensemble, rendering them significantly more expanded than generally inferred using fluorescence resonance energy transfer (FRET) measurements. We show here that fluo… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 86 publications
0
4
0
Order By: Relevance
“…Finally, fluorescent dye labeling was previously suggested to cause compaction of some intrinsically disordered proteins. For protein NLS, , it was attributed to the existence of a large number of charged residues. This result is consistent with the observation that the discrepancies in binding affinity measured using ITC and smFRET are dependent on ionic strength (Figure b), with a larger difference at lower ionic strengths.…”
mentioning
confidence: 99%
“…Finally, fluorescent dye labeling was previously suggested to cause compaction of some intrinsically disordered proteins. For protein NLS, , it was attributed to the existence of a large number of charged residues. This result is consistent with the observation that the discrepancies in binding affinity measured using ITC and smFRET are dependent on ionic strength (Figure b), with a larger difference at lower ionic strengths.…”
mentioning
confidence: 99%
“…In summary, we demonstrate that Trp can serve as either a FRET donor or a PET quencher to 4CN-Trp, a newly found blue fluorescent unnatural amino acid with a large fluorescence quantum yield (>0.8). The following considerations motivate this work: (1) spectroscopic techniques based on FRET and PET are widely used to assess protein conformations, conformational dynamics, and interactions; (2) evidence from several recent studies 10,11 indicate that using dye-based fluorophores in FRET and PET applications can yield skewed results, due to specific or preferred probe-probe interactions. Therefore, development of amino acid-based FRET and PET pairs that are intrinsically less-perturbative and hence can minimize such pitfalls is needed; (3) the absorption spectrum of 4CN-Trp is significantly red-shifted from that of Trp, allowing selective excitation of its fluorescence (e.g., using λ ex = 330−360 nm) or that of Trp (e.g., using λ ex = 270 nm) in PET or FRET applications; (4) 4CN-Trp is only one atom larger than Trp, making it less perturbative to proteins than fluorescent dyes; (5) 4CN-Trp can now be conveniently synthesized via chemical 28 and bilogical 29 means; and (6) it is possible to incorporate 4CN-Trp into proteins genetically via amber codon suppression or chemically using a post-translational modification method.…”
Section: Discussionmentioning
confidence: 99%
“…For example, several recent studies showed that many commonly used fluorescent dyes could interact with each other, causing inaccurate results in protein conformational studies. 10,11 Also, labeling a protein with two dyes through chemical reactions with amino acid sidechains could yield incomplete or unwanted products, hence leading to undesirable spectroscopic results. 8,12 Recently, Hilaire et al 13 found that the absorption and emission spectra of 4CN-Trp (and its fluorophore 4CN-indole) are significantly red-shifted from those of Trp (and indole).…”
Section: Introductionmentioning
confidence: 99%
“…Nearly all single-molecule approaches use extrinsic labels, and while these labels provide important contrast and specificity (10), label-free approaches that avoid arduous dye labeling procedures which may perturb the native functionality of biomolecules (11)(12)(13) are an increasingly desirable alternative. Most single-molecule approaches, including all current label-free methods, also rely on surfaces for immobilization, which is a costly compromise, as the measurement may bias detection towards sub-populations in mixed samples, disrupt native molecular interactions, alter dynamics, and generally precludes quantifying valuable solution-phase properties such as the diffusion constant (9,14,15).…”
Section: Introductionmentioning
confidence: 99%